2009
DOI: 10.1364/josab.26.000734
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic resonances of a multilayer metal-dielectric stack

Abstract: The electromagnetic resonances of multilayer metal-dielectric stacks are investigated. These structures support periodic bandpass regions, whose band edges may be predicted by considering the character of the fields inside the different layers. It is shown that the response of the structure is largely independent of its overall length, and that only the geometry of the unit cell is important. In the metal layers, the fields may have either a cosh or a sinh distribution function and match to standing waves insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…2͒ occur when sine-or cosine-like standing-waves in the dielectric layers couple via exponential fields within the metamaterial layers. Our experimental geometry is similar to that recently studied analytically by Gadsdon et al 16 who considered alternating layers of untextured metal and dielectric films in the visible regime. They showed that the metal film acts as a tunnel barrier, with the fields within the metal films taking either a hyperbolic sine or hyperbolic cosine form.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…2͒ occur when sine-or cosine-like standing-waves in the dielectric layers couple via exponential fields within the metamaterial layers. Our experimental geometry is similar to that recently studied analytically by Gadsdon et al 16 who considered alternating layers of untextured metal and dielectric films in the visible regime. They showed that the metal film acts as a tunnel barrier, with the fields within the metal films taking either a hyperbolic sine or hyperbolic cosine form.…”
mentioning
confidence: 56%
“…Importantly, this field solution is unlike that for an all dielectric multilayer stack. 5 ͑Note that the hyperbolic parts of the field distribution do not occur symmetrically in the second and fourth metamaterial layers due to the impedance mismatch with free space at the top and bottom of the stack.͒ The consequence of this result is particularly striking when one considers the effect of an increase of the number of repeat units in the stack 16 from four to ten ͑see Fig. 4͒: the lowest frequency mode ͑A͒ does not significantly move.…”
mentioning
confidence: 99%
“…It has been demonstrated that, near either band edge, there is a large enhancement of the field intensity due to localization effects [10,11]. Near the high-frequency band edge of the lowest frequency bandpass region, the electromagnetic field is predominantly confined to the dielectric regions in a manner similar to a stack of Fabry-Perot cavities, while at the low-frequency band edge, the fields are more concentrated in the metal regions [10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have explained the formation of the bandpass regions as being due to the matching of the tangential electric and magnetic fields associated with standing cavity modes in the dielectric, which may have either a cos or a sin wave character, and evanescent standing modes in the metal, which may have either a cosh or a sinh distribution function [10].…”
Section: Introductionmentioning
confidence: 99%
“…With the latest developments in fabrication technology, the transmission and reflection spectra of these structures can be realized at optical, [1][2][3][4] infrared, 5,6 terahertz, [7][8][9] and microwave [10][11][12][13] frequencies through careful design of the constituent subwavelength periodic elements and dielectric layers. For example, these include a stack of metal apertures (mesh-grids) at microwave 12 and infrared frequencies, 5,6 a stack of metallic patch arrays at microwave frequencies, 13 metal-dielectric and aperture/mesh-grid-dielectric stacks at optical frequencies, [1][2][3][4] and more recently a stack of graphene sheets-dielectric layers at low-terahertz frequencies. 9 Various periodically patterned graphene surfaces [14][15][16][17][18] have been designed at microwave, terahertz, and optical frequencies for tunable metamaterials, with potential applications including filters, absorbers, and polarizers.…”
Section: Introductionmentioning
confidence: 99%